The effect of electoral autocracy in Egypt's failed transition: a party politics perspective. (14th May 2019) - Resta, Valeria
Abstract: Although the failed democratic transition in Egypt following the Arab Spring is unanimously held as a poster child for the stubbornness of authoritarianism in the MENA region, its determinants remain disputed. Contributing to this debate, this article focuses on the noxious effects of past electoral authoritarianism on the transitional party system. More specifically, through quantitative text analysis, the article demonstrates that transitional parties' agency is largely the by-product of the way in which political competition was structured under the previous electoral autocracy. On the one hand, the uneven structure of opportunity upholding previous rule is central to the lack of pluralism. On the other hand, the previous regime's practice of playing opposition actors against each other through identity politics is at the root of the absence of common ground among the aforementioned parties during the transition.